Mollification of Diabetic Nephropathy in Streptozotocin-Induced Diabetic Mice Using Bitter Gourd Extract and ZnO Nanoparticles (Journal of the Bangladesh Agricultural University, 2025)
The study was carried out to evaluate the efficacy of bitter gourd extract (BGE) and zinc oxide nanoparticles (ZnONPs) against streptozotocin (STZ) induced diabetes nephropathy (DN) in male Swiss Albino mice. Multiple intraperitoneal (IP) injection of STZ was used to induce diabetes in experimental mice and were divided into five groups viz., T0 = control (no diabetes and no treatment), T1 = STZ-induced DN without treatment, T2 = STZ-induced DN treated with BGE, T3 = STZ-induced DN treated with ZnONPs and T4 = STZ-induced DN treated with both BGE and ZnONPs. The respective groups received single oral daily dose of BGE @ 5g kg-1 body weight and ZnONPs @ 8 mg kg-1 body weight, where control and T1  groups were given normal distilled water orally. Data were recorded on blood glucose level, blood urea nitrogen levels and serum creatinine at 5 days after STZ administration and thereafter 7, 14 and 21 days after administration of bitter gourd extract and ZnO nanoparticles. Bitter gourd extract and ZnONPs were found operative to reduce the blood glucose level, creatine level and blood urea nitrogen level in nephropathic mice where combined effect was more effective than the individual effects against diabetic nephropathy. The findings provide considerable evidence about the efficacy of BGE and ZnONPs which could help to design the clinical application of BGE and ZnONPs on a standardized formulation to protest the development of diabetic nephropathy. However, BGE and ZnONPs possess a potential anti-diabetic as well as anti-nephropathic activity, which could be validated by further mechanistic investigations.J Bangladesh Agril Univ 23(2): 166-174, 2025